2021
DOI: 10.1016/j.lfs.2021.119881
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo protection from SARS-CoV-2 infection by ATN-161 in k18-hACE2 transgenic mice

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an infectious disease that has spread worldwide. Current treatments are limited in both availability and efficacy, such that improving our understanding of the factors that facilitate infection is urgently needed to more effectively treat infected individuals and to curb the pandemic. We and others have previously demonstrated the significance of interactions between the SARS-CoV-2 spike protein, integrin α5β1, and human ACE2 to facilitate viral e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 76 publications
(110 reference statements)
1
26
0
Order By: Relevance
“…Of interest, one motif was found to be similar to the ATN-161 pentapeptide, which has been shown to block against SARS-CoV-2 infection in vivo ( Amruta et al, 2021 )⁠. The RGD-based drug, Cilengitide, and the RGD peptide were also found to inhibit spike-integrins interactions on endothelial cells ( Nader et al, 2021 ; Robles et al, 2021 )⁠.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, one motif was found to be similar to the ATN-161 pentapeptide, which has been shown to block against SARS-CoV-2 infection in vivo ( Amruta et al, 2021 )⁠. The RGD-based drug, Cilengitide, and the RGD peptide were also found to inhibit spike-integrins interactions on endothelial cells ( Nader et al, 2021 ; Robles et al, 2021 )⁠.…”
Section: Discussionmentioning
confidence: 99%
“…This was also the case for the similarity between the ATN-161 pentapeptide sequence (PHSCN) and the spike STPCN motif, in which both the P and S residues are present but in a different order. Furthermore, the similarity to the ATN-161 pentapeptide is interesting considering studies that suggest its protective ability against SARS-CoV-2 infection, although the peptide has been suggested to also bind the RGD-binding site on integrins ( Amruta et al, 2021 ; Beddingfield et al, 2021 )⁠. Structural analysis to investigate the accessibility of the motifs on the spike protein may lend more insights into their potential ability to bind integrins.…”
Section: Non-rgd Potential Integrin-binding Motifs On the Sars-cov-2 Spike Protein Receptor-binding Domainmentioning
confidence: 99%
“…Together, the combination of multiple transgenic hACE2-expressing mouse models under various promoters, adenovirus-based methods for transduction of multiple mouse strains with hACE2, mouse-adapted SARS-CoV-2 strains, and the susceptibility of mice to emerging VOC has resulted in laboratory mice becoming highly useful models for SARS-CoV-2 infection studies and efficacy testing of vaccines and therapeutics [ 220 , 221 , 222 , 223 , 224 ].…”
Section: Main Textmentioning
confidence: 99%
“…Our laboratory has shown that endothelial cell-specific integrin α5β1 gene deficiency results in significant resistance to ischemic stroke injury in mice [ 11 ]. Furthermore, treatment with a novel α5β1 integrin inhibitor, the pentapeptide ATN-161, reduces neuroinflammation, stabilizes ECM remodeling and is neuroprotective in murine ischemic stroke and protection from SARS-CoV-2 infection in k18-hACE2 transgenic mice [ 12 , 8 ]. To further elucidate ATN-161’s precise therapeutic mechanisms of action, we studied ATN-161 in an in vitro model of stroke, oxygen–glucose deprivation/reoxygenation (OGD/R) in brain endothelial cells.…”
Section: Introductionmentioning
confidence: 99%